Delayed presentation for human immunodeficiency virus (HIV) care among veterans: a problem of access or screening? - Gandhi, Neel R; Skanderson, Melissa; Gordon, Kirsha S; Concato, John; Justice, Amy C (Medical care, 2007)
Despite the effectiveness of antiretroviral therapy, nearly half of patients entering human immunodeficiency virus (HIV) care have advanced disease. Many attribute this delay to poor access to healthcare. Others argue that delays will persist until routine screening is adopted. The Veterans Health Administration (VA) is a unique laboratory to examine whether access to comprehensive health benefits results in earlier entry into HIV care.
Keywords: Acquired Immunodeficiency Syndrome; CD4 Lymphocyte Count; Female; Health Services; Health Services Accessibility; HIV Infections; Humans; Male; Middle Aged; Retrospective Studies; United States; Veterans